The need for a cultural landscape theory. An architect's approach. - Calcatinge, Alexandru (Lit, 2012)
Can aesthetics and ethics be integrated for the good of habitats, places and spaces? How can arts widen our perception of nature and deepen environmental ethics? Should the political meaning of a landscape be defined solely in terms of its economic and ecological values? Questions like these are explored from the angles of arts, environmental ethics, ecology, religious studies, theology, art history and philosophy. The book catalyzes the reflection about the aesthetic and spiritual dimension in the environmental humanities, and it offers transdisciplinary insights into the challenge of sustainability and ongoing changes in the society and our environment.
Keywords: Landschaft; Landschaftsplanung; Kulturlandschaft; Planungstheorie; Landschaftsbild; Raumtheorie; Szenario; Raumwahrnehmung; Raumbegriff; Ideengeschichte